Kvalita poskytované péče očima pacientů ve vztahu ke strategickému managementu ve vybrané zdravotnické organizaci - Maříková, Irena; Jankůj, Miroslav; Vysoká škola ekonomická v Praze. Fakulta managementu; Střítecký, Rudolf, 1946-2018 (2015)
The aim of the thesis is to make the strategic analysis of the specific medical device in relation to quality of health care from the view of its patients. In this thesis are used selected analysis instruments of the strategic management. For finding of the quality of the health care, which the medical device provides, I used investigation through questionnaires. Information I gained through these questionnaires I have evaluated and analysed this data. The medical device I have chosen doesn't wish to be named in my thesis so I will respect the wish of its management. This hospital is located in The Central Bohemian Region, which is also its founder. This institution provides inpatient and outpatient care. The mail strength of the hospital is its employees and their human potential. On the other hand one of the serious weaknesses is the poor marketing productivity. My thesis will be closed with appropriate recommendations for the hospital which will be based on my analyses. The intention of these recommendations is to help the hospital in its future development. My thesis goes from the theoretical part (which explains the issue) and fallows with the practical part.
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2015
Vedoucí práce: Miroslav Jankůj
Obsahuje bibliografii
Rok obhajoby 2015
Keywords: zdravotnický management; strategický management; management jakosti; management [obor dipl. práce]; diplomové práce; health service management; strategic planning; quality control; master's theses